Tourist Market Segmentation by Motivation to Shop: A Case Study of Istanbul, Turkey - Egresi, István (Geographica Pannonica, 2017)
Previous research has indicated that shopping could make up for a significant part of the tourist experience and could provide significant benefits to destinations by contributing to local retail revenue and by generating many jobs. In order to design better marketing strategies, destination managers must understand what attracts tourists to a destination and makes them shop while there. However, tourists represent a heterogeneous group and subgroups of individuals are motivated to visit a destination for a variety of reasons. The primary purpose of this study is to segment tourist shoppers visiting Istanbul according to their motivation to shop. Five distinctive groups of ‘product-focused shoppers’, ‘shoppers for cultural experience’, ‘reluctant shoppers’, ‘difference seekers’ and ‘total shoppers’ were found and compared by the geographical origin of the tourists, their socio-demographic characteristics, travel characteristics and behaviour, primary motivation for the trip, activity participation and shopping preferences and attitudes. The findings indicate that destination marketers must develop their strategies and marketing products to address the heterogeneity of motivations underlying tourist shopping.